Un calendrier vaccinal pour les personnes âgées de plus de 65 ans - Doiron, Jessica; Turmel, Patrick; Morin, Gabrielle; Lessard, Catherine; Côté, Hélène; Grenier, Jean-Luc; Mallet, Louise (Pharmactuel, 2015)
-